Efek Perbedaan Pelarut terhadap Uji Toksisitas Ekstrak Pineung Nyen Teusalee - Hilka Yuliani; Maya Indra Rasyid (Faculty of Pharmacy, Universitas Muslim Indonesia, 2019)
Smoked young areca nut seed or pineung nyen teusalee is a material commonly used by the Acehnese as medicine, especially diabetes medicine. This study aims to determine the phytochemical content and toxicity level of pineung nyen teusalee extracted using ethanol and aquadest. The concentration of pineung nyen teusalee extract solution used as the toxicity test concentration was 0 mg / L, 50 mg / L, 100 mg / L, 500 mg / L, and 1000 mg / L. Qualitative methods were used in testing phytochemical compounds while the toxicity level of LC50 using probit analysis using SPSS version 16.0 software. From the results of phytochemical analysis tests (flavonoids, tannins, and saponins) positive results were obtained for ethanol extract and aquadest extract for all phytochemical test parameters. Probit analysis showed that the concentration of ethanol extract of pineung nyen teusalee had a toxic effect on 50% of the population of Artemia salina Leach larvae with LC50 values of 115.71 mg/L. While the concentration of aquadest extract of pineung nyen teusalee gave an LC50 value of 338.40 mg/L.